2011
DOI: 10.1007/s11136-010-9834-y
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the PedsQL™ Multidimensional Fatigue Scale in Japan

Abstract: The Japanese-language version of the PedsQL™ Multidimensional Fatigue Scale demonstrated good reliability and validity and could be useful in evaluating Japanese children in school and health care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 39 publications
5
27
2
2
Order By: Relevance
“…Reasonable values of convergent and divergent validity were also observed, indicating construct validity similar to that demonstrated for a Japanese version of this scale (Kobayashi et al, 2011). Furthermore, root mean square error of approximation values were within acceptable limits, pointing to the preservation of the factorial structure in the model adapted for Brazil.…”
Section: Journal Of Pediatric Oncology Nursingsupporting
confidence: 64%
“…Reasonable values of convergent and divergent validity were also observed, indicating construct validity similar to that demonstrated for a Japanese version of this scale (Kobayashi et al, 2011). Furthermore, root mean square error of approximation values were within acceptable limits, pointing to the preservation of the factorial structure in the model adapted for Brazil.…”
Section: Journal Of Pediatric Oncology Nursingsupporting
confidence: 64%
“…This is not unexpected given that items within this domain measure memory and attention, and prior findings in patients with stroke demonstrated significantly lower Cognitive Fatigue Scale scores in comparison to healthy children . It should be noted that the Cognitive Fatigue Scale has demonstrated differences between healthy children and pediatric patients with expected cognitive functioning problems . Additionally, recent analyses of factorial invariance across age and gender for the PedsQL™ MFS have indicated that a bifactor model is appropriate; that is, a bifactor model of the 18 items with one general factor (fatigue) influencing all the items and three domain‐specific factors representing the General, Sleep/Rest, and Cognitive Fatigue domains .…”
Section: Discussionmentioning
confidence: 67%
“…Consequently, the objective of this study was to examine feasibility, internal consistency reliability, construct validity, and known‐groups discriminant validity of the PedsQL™ MFS in pediatric patients with SCD. We hypothesized the measure would distinguish between patients with SCD and healthy children , supporting known‐groups discriminant validity. We expected the PedsQL™ MFS would be significantly correlated with the PedsQL™ Generic Core Scales, with medium to larger effect sizes, based on the conceptualization of symptoms as causal indicators of generic HRQOL , supporting construct validity.…”
Section: Introductionmentioning
confidence: 78%
“…The Japanese version of the Pediatric Quality of Life Inventory (PedsQL) Multidimensional Fatigue Scale was used to evaluate children's fatigue. The measure consists of 18 items, each rated on a 5 point Likert scale (0, never a problem to 4, almost always a problem), which comprise three subscales: General, Sleep/Rest, and Cognitive Fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…The average scores are calculated using a linearly transformed reversed score ranging from 0 to 100, so that higher scores indicate fewer symptoms of fatigue. This measure has adequate internal consistency reliability (Cronbach's α coefficient, 0.81–0.93) …”
Section: Methodsmentioning
confidence: 99%